Influence of Leadership Factors on the Work Engagement of Uniformed Police Officers (Journal of Universal Excellence, 2026)
Research question (RQ): Are any statistically significant correlations between the factors in the management of the police and the degree of engagement between uniformed police officers.Purpose: The aim of this master’s thesis is to examine the influence of leadership factors on the work engagement of uniformed police officers in the analysed police stations, as well as to provide recommendations for improvement. Methodology: A quantitative survey was conducted among 932 uniformed police officers from all 22 police stations of the Police Directorate Ljubljana. Results: No positive correlation was found between elements of police station leadership and the level of work engagement of uniformed police officers. A positive correlation was identified between the level of work engagement of uniformed police officers and length of service. There was no positive correlation between leadership factors and the police officers’ posts. Organization: The findings will be of practical use to police station managers of Police Directorate Ljubljana in planning, organizing, leading, and controlling. They can also serve as a foundation for other researchers to conduct further research on the subject with the help of additional data.Originality: Based on the survey data, we identify and clarify the factors keeping on Police stations and factors engagement uniformed police officers at police stations. We have gained new knowledge that cannot be read in the domestic and foreign literature, with which we have contributed to the upgrading of existing knowledge.Limitation:  The survey was carried out between uniformed police officers at police stations in the area of the Ljubljana Police Directorate, and the results from the study cannot be generalized to all Police stations in Slovenia.
Keywords: survey; police station; research; uniformed police officer; leadership; employee engagement